PILOMATRIXOMA OF FACE PRESENTING AS PAROTID SWELLING - Zaidi, Hira; Hanif, Arsia; Ahmed, Salman Niaz; Khyani, Iqbal A. M (International Journal of Research -GRANTHAALAYAH, 2021)
Pilomatrixoma, also known as pilomatrixoma or calcifying epithelioma of Malherbe, is a benign tumor of skin appendages. Although it is an uncommon and benign neoplasm of the head and neck region, it may sometimes become malignant. It arises from the cells of the outer sheath of the hair follicle root. Owing to its rarity, pilomatrixoma can be missed during differential diagnosis, and it can be misdiagnosed as malignancy. Therefore, for definitive and confirmatory diagnosis, histopathological analysis is imperative. We report a case of a 26-year-old female who presented with hard swelling on the right side of her face near the angle of the mandible. We have discussed its clinical, radiological, and histological findings and reflected light on the treatment of choice for pilomatrixoma.